Optimalisasi Sistem Kemitraan Waralaba Untuk Meningkatkan Perekonomian Lokal Di Kota Tangerang Selatan - Mohammad Rizky Axell Putranto; Yanda Bara Kusuma (Universitas Kristen Indonesia Toraja, 2023)
Micro, Small and Medium Enterprises (MSME) have a strategic role in improving the national economy. South Tangerang City is one of the cities in Indonesia which has a fairly large number of MSME. However, MSME in Tangerang Selatan City also experience various difficulties in business such as difficulties in capital, obtaining raw materials, marketing products, and other operational matters. Optimizing franchise partnerships is a solution that can be done. Franchise Partnership Business is a special right owned by an individual or business entity to a business system with business characteristics in the context of marketing goods or services that have been proven successful and can be utilized by other parties based on a Franchise Agreement. The method used is descriptive qualitative which is useful for describing phenomena that occur in the field by collecting data from various sources, such as books, journals and other related documents. Based on the data obtained, the number of MSME in Tangerang Selatan City is very large. Therefore, with the existence of a franchise business partnership system, the development of MSME in Tangerang Selatan can be far more developed and can also improve the local economy.